The Drosophila Stubble-stubbloid gene encodes an apparent transmembrane serine protease required for epithelial morphogenesis. - Appel, L.F.; Prout, M.; Abu-Shumays, R.; Hammonds, A.; Garbe, J.C.; Fristrom, D.; Fristrom, J. (Proceedings of the National Academy of Sciences of the United States of America, 1993)
The Stubble-stubbloid (Sb-sbd) gene is required for hormone-dependent epithelial morphogenesis of imaginal discs of Drosophila, including the formation of bristles, legs, and wings. The gene has been cloned by using Sb-sbd-associated DNA lesions in a 20-kilobase (kb) region of a 263-kb genomic walk. The region specifies an approximately 3.8-kb transcript that is induced by the steroid hormone 20-hydroxyecdysone in imaginal discs cultured in vitro. The conceptually translated protein is an apparent 786-residue type II transmembrane protein (N terminus in, C terminus out), including an intracellular N-terminal domain of at least 35 residues and an extracellular C-terminal trypsin-like serine protease domain of 244 residues. Sequence analyses indicate that the Sb-sbd-encoded protease could activate itself by proteolytic cleavage. Consistent with the cell-autonomous nature of the Sb-sbd bristle phenotype, a disulfide bond between cysteine residues in the noncatalytic N-terminal fragment and the C-terminal catalytic fragment could tether the protease to the membrane after activation. Both dominant Sb and recessive sbd mutations affect the organization of microfilament bundles during bristle morphogenesis. We propose that the Sb-sbd product has a dual function. (i) It acts through its proteolytic extracellular domain to detach imaginal disc cells from extracellular matrices, and (ii) it transmits an outside-to-inside signal to its intracellular domain to modify the cytoskeleton and facilitate cell shape changes underlying morphogenesis.